Features of the vegetative state and arterial pressure level in children with chronic gastroduodenal pathology - A. S. Hotsulia (Zaporozhye State Medical University, 2018)
Introduction. Heterocyclic compounds are the foundation on which the creation of medicines is successfully carried out. One such system is 1,2,4-triazole and 3-methylxanthine. These heterocycles are characterized by wide range of biological properties, along with low toxicity. The purpose of this work was to synthesize and investigate the properties of N-R-amides and hydrazides 2-[4-R-5-(3'-methylxanthine-7'-yl)-1,2,4-triazole-3-ylthio]acetic acid (R = CH3, C2H5, C6H5) when changing the conditions of the chemical process.Methods and results. As initial key reagents we used 7'-((3-thio-4-R-4H-1,2,4-triazole-5-yl)methyl)-3'-methylxanthine and ethers of 2-[4-R-5-((3'-methylxanthine-7'-yl)methyl)-1,2,4-triazole-3-ylthio]acetic acid, which were prepared according to known procedures from available raw materials. In the course of studies, it was found that when heated in ethanol the corresponding primary or secondary alkylamines (methylamine, ethylamine, monoethanolamine, diethylamine) or ammonia solution from prop-1-yl 2-[4-R-5-((3'-methylxanthine-7'-yl)methyl)-1,2,4-triazole-3-ylthio]ethanoate, then the corresponding amidated derivatives of 2-[4-R-5-((3'-methylxanthine-7'-yl)methyl)-1,2,4-triazole-3-ylthio]acetic acid are created. The corresponding amides were obtained by reacting 7'-((3-thio-4-R-4H-1,2,4-triazol-5-yl)methyl)-3'-methylxanthine with 2-chloroacetamide in a high yield sodium hydroxide medium. Hydrazides of 2-[4-R-5-((3'-methylxanthine-7'-yl)methyl)-1,2,4-triazole-3-ylthio]-ethane acid are synthesized by the interaction of the corresponding esters of 2-[4-R-5-((3'-methylxanthine-7'-yl)methyl)-1,2,4-triazole-3-ylthio]acetic acid with an aqueous hydrazine hydrate solution in ethanol. The structure of the obtained compounds is confirmed by the data of elemental analysis, 1H NMR spectroscopy, IR-spectrophotometry. Individuality was established using thin-layer chromatography and chromatography-mass spectrometry. For synthesized compounds, preliminary screening was performed using the PASS On-line® software and molecular docking.The optimal methods for the preparation hydrazides and amides of 2-[4-R-5-((3'-methylxanthine-7'-yl)methyl)-1,2,4-triazole-3-ylthio]ethane acid were developed. The production of amides in two alternative pathways using the starting thiol and the ester, derived from it, was studied: it was established that the interaction of the starting thiol with 2-chloroacetamide runs with a larger yield of the reaction product in comparison with the reaction of the corresponding ester with ammonia. The results of physical-chemical analysis of synthesized compounds was interpreted. This preliminary assessment of the possible manifestation of anti-inflammatory activity was given. The probability of manifestation of this type of activity was not high.Conclusions. 19 amides and 3 hydrazide of 2-[4-R-5-((3'-methylxanthine-7'-yl)methyl)-1,2,4-triazole-3-ylthio]ethane acid were obtained with high yields and purity, their structure was proven and properties were investigated.